2015
DOI: 10.2139/ssrn.2650428
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Care Reform and the Labor Supply of Household Members: Evidence from a Quasi-Experiment

Abstract: Long-term care reform and the labor supply of household members: Evidence from a quasiexperiment Ruhr Economic Papers, No. 574 Provided in Cooperation with: RWI -Leibniz-Institut für Wirtschaftsforschung, Essen Suggested Citation: Geyer, Johannes; Korfhage, Thorben (2015) : Long-term care reform and the labor supply of household members: Evidence from a quasi-experiment, Ruhr Economic Papers, No. 574, The working papers published in the Series constitute work in progress circulated to stimulate discussion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Since the Dutch LTC system is very generous, our findings can be reconciled with studies from other countries reporting labour market effects of less generous LTC system policy reforms (e.g. Fu et al, 2017;Geyer and Korfhage, 2017).…”
Section: Introductionsupporting
confidence: 79%
“…Since the Dutch LTC system is very generous, our findings can be reconciled with studies from other countries reporting labour market effects of less generous LTC system policy reforms (e.g. Fu et al, 2017;Geyer and Korfhage, 2017).…”
Section: Introductionsupporting
confidence: 79%
“…Geyer and Korfhage (2015) estimate that cash subsidies in Germany reduced the labour participation, while supports exert a small positive effect. Similarly, Geyer and Korfhage (2017) found that the extension of long-term care subsidies and supports did not shift the labour supply of women but had a negative effect on that of men (-19.3 pp). Similarly, Korfhage (2019) reported that cash benefits encourage the provision of informal care and the exit from the labour market of individuals among lower income individuals.…”
Section: Gender Differences In Caregivingmentioning
confidence: 93%
“…Given that traditional caregivers tend to be close to retirement age, a contribution to this debate lies in examining the effect of caregiving incentives on the exit of the labour market decisions, and more specifically the effect of caregiving on caregiver's early retirement intentions (Dentinger and Clarkberg, 2002;Schils, 2008;Debrand and Sirven, 2009;Meng, 2011;King and Pickard, 2013;Jacobs et al, 2014;Geyer and Korfhage, 2015;Geyer and Korfhage, 2017;Jacobs et al, 2017). This is an important question as early retirement can widen the pension income gap between caregivers and noncaregivers, which in turn puts the sustainability of the pension system at risk (Boeri et al, 2001;General Secretariat of the Council, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the effects of the German LTCI on carers' labor supply have only once been analyzed in an econometric setting. Geyer and Korfhage () examine the labor supply effects of the introduction of the LTCI in 1995 for co‐residential carers. Using a difference‐in‐differences approach, the authors find a negative effect for men and no significant effect for women.…”
Section: Introductionmentioning
confidence: 99%